Rancang Bangun Alat Bleeding Brake Fluid untuk Mempermudah Proses Pengujian Sistem Rem Mekanik - Muhammad Farhan; Adri Pato (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
The hydraulic braking system is one of the primary safety components in motor vehicles, functioning to reduce speed and stop the vehicle safely. Brake system performance is strongly influenced by the condition of the brake fluid and the absence of trapped air within the hydraulic lines. In most automotive workshops, the brake bleeding process is still performed manually by two operators, resulting in relatively long processing times and inconsistent bleeding quality. This study aims to design and develop a Brake Fluid Bleeding Device to simplify the testing process of mechanical braking systems and improve bleeding efficiency. The research method consisted of design, prototype fabrication, functional testing, and performance evaluation by comparing the conventional manual bleeding method with the developed device. The evaluated parameters included bleeding time, the number of required operators, and the effectiveness of air removal from the hydraulic braking system. The results indicate that the developed device simplifies the bleeding process, allowing it to be operated by a single operator while reducing the processing time compared to the conventional method. Furthermore, the device provides a more stable bleeding process, thereby improving braking system performance. The proposed brake fluid bleeding device has the potential to be implemented in automotive workshops as an alternative maintenance tool to improve work efficiency and service quality.